Upaya Hukum yang Dapat Diambil Konsumen Terkait Keterlambatan dalam Proses Pengiriman Produk - Indra Indra; Agustianto Agustianto; Nadia Carolina Weley (SENTRI: Jurnal Riset Ilmiah, 2026)
Delays in delivery of goods in e-commerce transactions in Indonesia cause material and immaterial losses for consumers. This situation places customers at a disadvantage and requires a firm regulatory framework to enforce their rights. The objective of this study is to analyze the regulatory arrangements that control delivery delays, the obligations of businesses and delivery services, and the mechanisms for customers facing default. The method applied is a doctrinal juridical study through regulatory methodology and an empirical study in the form of a survey and literature review related to e-commerce practices, customer protection, and default. The study findings indicate that legal regulations regarding delivery delays are quite comprehensive, reflected in Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions, Government Regulation Number 71 of 2019, and delivery service regulations. However, practice in the field shows a gap between legal norms and reality, with more than 35% of consumers experiencing delays at least once a year due to internal business factors or logistical constraints. Consumers can pursue non-litigation legal remedies through complaints, grievances, or BPSK (the Consumer Protection and Security Agency), as well as litigation in the form of breach of contract lawsuits and demands for material and immaterial compensation. This study concludes that the success of legal customer protection depends heavily on regulatory implementation, coordination between businesses and delivery services, and consumers' understanding of their rights.